Estimulação magnética transespinhal theta-burst associada ao treinamento em esteira no equilíbrio postural de pessoas com doença de Parkinson: estudo piloto randomizado cruzado - Melo, Maria Clara Silva de (2024)
Introduction: Postural instability is a significant limitation in Parkinson's Disease (PD) that is refractory to dopaminergic treatment. Objective: To compare two distinct protocols of Theta Burst repetitive Transspinal Magnetic Stimulation (rTSMS) combined with treadmill training on postural balance in individuals with PD. Method: A pilot randomized, single-blind, crossover clinical trial conducted at the Federal University of Paraíba. Participants included individuals with idiopathic PD between stages 1.5 and 4 according to the modified Hoehn & Yahr scale, who reported postural instability. The primary outcome, postural balance, was assessed using the MiniBest Test before the initiation of the protocol and immediately after the first and second phases of the study, during which participants received different doses of rTSMS pulses (60 trains and 20 trains) over 5 consecutive days. Secondary outcomes included fear of falling, turning ability, quality of life, and motor function. Results: Ten individuals with PD participated, with a mean age of 64.20 ± 7.46 years, a diagnosis duration of 129.40 ± 110.24 months, and predominantly presenting with the akinetic-rigid phenotype (50%). Treatment with 60 trains of rTSMS resulted in a significant change in postural balance (p = 0.025) and motor function (p = 0.020). No significant changes were observed between treatments for turning ability (p > 0.05), quality of life (p = 0.208), and fear of falling (p = 0.591). Seventy percent of participants reported improved balance, and 40% reported enhanced postural stability. Conclusions: The rTSMS stimulation protocol with 60 trains resulted in modifications in postural balance and a reduction in fall risk in individuals with PD.